2021
DOI: 10.1111/bjet.13054
|View full text |Cite
|
Sign up to set email alerts
|

Peer feedback or peer feedforward? Enhancing students’ argumentative peer learning processes and outcomes

Abstract: This study compared the effects of support for peer feedback, peer feedforward and their combination on students’ peer learning processes, argumentative essay quality and domain‐specific learning. Participants were 86 BSc students who were randomly divided over 43 dyads. These dyads, in a two‐factorial experimental design, were assigned to four conditions including: peer feedback (n = 22), peer feedforward (n = 22), mixed (n = 20) and control group (n = 22) conditions. An online peer feedback environment named… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(34 citation statements)
references
References 48 publications
4
29
0
1
Order By: Relevance
“…CW tasks have proven to enhance EFL learners' writing skills on an individual level. The findings are congruent with previous studies (e.g., Alghasab et al, 2019Dobao, 2014;Latifi et al, 2021) which reported that EFL learners who were exposed to CW practice could improve text quality including essay organization and grammar when they subsequently produced texts on an individual basis. We found that learners produced shorter but more accurate and complete sentences.…”
Section: Cw Improves Learners' Writing Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…CW tasks have proven to enhance EFL learners' writing skills on an individual level. The findings are congruent with previous studies (e.g., Alghasab et al, 2019Dobao, 2014;Latifi et al, 2021) which reported that EFL learners who were exposed to CW practice could improve text quality including essay organization and grammar when they subsequently produced texts on an individual basis. We found that learners produced shorter but more accurate and complete sentences.…”
Section: Cw Improves Learners' Writing Performancesupporting
confidence: 90%
“…The domain on "language use" improved by 2.67 points in the posttest mean score, and "mechanics" 0.50 score on a five-point scale. The findings were in line with and Latifi et al's (2021) studies which found that EFL learners who were exposed to CW practice and received peer feedback outperformed their peers who were not, in terms of accuracy and text quality, which includes organization, vocabulary, and grammar when they subsequently produced texts on an individual basis in a delayed post-test writing. In other words, the benefits of CW tasks can be translated into higher scores on subsequent individual writing.…”
Section: Analysis Of Writing Performancesupporting
confidence: 89%
“…In terms of the second research question whether scaffolding strategies used influenced learners' writing performance, the present findings seem to echo recent studies on CW (e.g., Alghasab et al, 2019;Latifi et al, 2021) which asserted that EFL learners who received CW training could eventually develop essay content and organization and improve their individual writing skills. In other words, the benefits of peer scaffolding negotiations while engaging in OCW tasks could be translated into better quality work when learners construct their own essays.…”
Section: Discussionsupporting
confidence: 81%
“…In the literature, a number of strategies were used, such as continuous assessment, peer assessment, feedback on drafts, and answers or comments provided by lecturers. Figure 3 presents the range of feedforward approaches that proved their effectiveness as constructive guidance for improving student development within the course beyond focusing on assessments, such as self-assessing [29], peer marking exercises [31,32], discussion of work-in-progress [33], past assessment evaluation and exemplars [34][35][36][37], submission of draft work [22], and feedforward interviews [38].…”
Section: Feedforward Approachesmentioning
confidence: 99%